Performance Enhancement of Motorcycle Engines Using Lemongrass Oil-Based Fuel Additive - Budi, Pangga Urip Setio; Suhara, Ade; Supriyanto, Agus; Patya, Dhea Intan; Khoirudin, Khoirudin; Nanda, Rizki Aulia (Journal of Mechanical Engineering, Science, and Innovation, 2025)
The increasing number of motor vehicles has led to higher fuel consumption, especially among two-wheeled vehicles, contributing to elevated emissions of hydrocarbon (HC) and carbon monoxide (CO). This study investigates the potential of lemongrass oil (LO) as natural additive to reduce exhaust emissions from RON 92 fuel. The LO was extracted via maceration and characterized by its physical properties, including density (0.893 g/mL), viscosity (5.30 mPa.s), and boiling point (222 °C), consistent with pure LO standards. The additive as then blended into RON 92 fuel in concentration of 10 mL, 15 mL, and 20 mL per 1000 mL of fuel to determine its optimal performance. Results showed that a 20 mL addition yielded the highest reduction in HC and CO emissions, respectively 49.76% and 46.24%. Furthermore, engine performance improved, with power increasing by 0.27 HP and torque by 0.21 Nm within an engine speed range of 5200-5700 rpm. These outcomes suggest that LO enhances combustion efficiency and reduces emissions. The findings highlight the potential of LO as an environmentally friendly fuel additive and supprt ongoing efforts to develop sustainable alternatives to conventional fossil fuels in Indonesia.